2004
DOI: 10.1038/sj.emboj.7600495
|View full text |Cite
|
Sign up to set email alerts
|

Capsule synthesis by Bacillus anthracis is required for dissemination in murine inhalation anthrax

Abstract: Bacillus anthracis, the agent of anthrax, produces a poly-Dglutamic acid capsule that has been implicated in virulence. Many strains missing pXO2 (96 kb), which harbors the capsule biosynthetic operon capBCAD, but carrying pXO1 (182 kb) that harbors the anthrax toxin genes, are attenuated in animal models. Also, noncapsulated strains are readily phagocytosed by macrophage cell lines, whereas capsulated strains are resistant to phagocytosis. We show that a strain carrying both virulence plasmids but deleted spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
165
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(171 citation statements)
references
References 35 publications
5
165
1
Order By: Relevance
“…The biosynthetic operon capBCADE encoding the capsule is present on the plasmid pXO2 (3)(4)(5)(6). Strains that lack pXO2 are highly attenuated (7)(8)(9), and such strains have been used as vaccines to prevent anthrax in domesticated animals for more than 50 y (10). In a mouse model of pulmonary anthrax, encapsulation was shown to be essential for dissemination from the lungs and for persistence and survival of the bacterium in the host (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The biosynthetic operon capBCADE encoding the capsule is present on the plasmid pXO2 (3)(4)(5)(6). Strains that lack pXO2 are highly attenuated (7)(8)(9), and such strains have been used as vaccines to prevent anthrax in domesticated animals for more than 50 y (10). In a mouse model of pulmonary anthrax, encapsulation was shown to be essential for dissemination from the lungs and for persistence and survival of the bacterium in the host (7).…”
mentioning
confidence: 99%
“…Strains that lack pXO2 are highly attenuated (7)(8)(9), and such strains have been used as vaccines to prevent anthrax in domesticated animals for more than 50 y (10). In a mouse model of pulmonary anthrax, encapsulation was shown to be essential for dissemination from the lungs and for persistence and survival of the bacterium in the host (7). Virulence appears to be associated with antiphagocytic properties of the capsule (5,11,12).…”
mentioning
confidence: 99%
“…The B. anthracis capsule (pX02) and toxin (pX01) plasmids encode factors that enhance survival in the host, likely in part by subverting the bactericidal activity of neutrophils. The capsule is essential for virulence (3,10,18,21), and its antiphagocytic property is a primary mechanism of immune cell evasion utilized by B. anthracis (21,22,26). The anthrax lethal toxin (PA plus LF) and edema toxin (PA plus EF) are known to inhibit some neutrophil functions (1,8,12,21,34,43), but in contrast to a deleterious effect of lethal toxin on macrophage survival from some animals (13,14), neither affects human neutrophil viability (8).…”
mentioning
confidence: 99%
“…4,5 Like many microbial capsules, PGA has a high molecular weight, is resistant to degradation, and presents a significant barrier to the mammalian immune system. [6][7][8][9] Previous studies identified the capsule as a potential therapeutic target in both active and passive immunization strategies. [10][11][12] Capsule-binding antibodies increase opsonization and phagocytosis of vegetative bacteria.…”
Section: Introductionmentioning
confidence: 99%